2014
DOI: 10.1016/j.toxrep.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perfluorooctanoate for potential genotoxicity

Abstract: Perfluorooctanoate (PFOA) is a fully fluorinated eight-carbon fatty acid analog with exceptional stability toward degradation that has been used as an industrial surfactant and has been detected in environmental and biological matrices. Exposures to PFOA in the workplace and in the environment have continuously stimulated investigations into its potential human health hazards. In this article, the results of fifteen unpublished genotoxicity assays conducted with perfluorooctanoate (as either the linear or line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…No genotoxicity was reported in HepG2 cells exposed to PFOA, PFOS, perfluorobutane sulfonate, PFNA, and PFHxA, in parallel to our results (Eriksen et al, 2010; Florentin et al, 2011). It was also concluded that PFOA did not show any direct mutagenic or genotoxic effect (Butenhoff et al, 2014). Unlike several studies in which similar negative results were obtained, the genotoxic effect was observed in HepG2 cells exposed to PFOA, PFHxS, PFOS, PFOA, and PFNA (Wielsøe et al, 2015; Yao and Zhong, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…No genotoxicity was reported in HepG2 cells exposed to PFOA, PFOS, perfluorobutane sulfonate, PFNA, and PFHxA, in parallel to our results (Eriksen et al, 2010; Florentin et al, 2011). It was also concluded that PFOA did not show any direct mutagenic or genotoxic effect (Butenhoff et al, 2014). Unlike several studies in which similar negative results were obtained, the genotoxic effect was observed in HepG2 cells exposed to PFOA, PFHxS, PFOS, PFOA, and PFNA (Wielsøe et al, 2015; Yao and Zhong, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of unpublished genetic toxicity test data generated in industry-sponsored studies, PFOA, tested as either an ammonium or sodium salt, was found to be negative in bacterial mutagenicity assays, in the CHO/HGPRT forward mutation assay, in the chromosomal aberration assay when performed using CHO cells or primary human lymphocytes, and in the mouse bone marrow micronucleus assay 99 .…”
Section: Genetic Toxicitymentioning
confidence: 99%
“…Little or no information is available for other long-F-chain PFASs. Numerous studies involving multiple assays found no direct mutagenic or genotoxic risk associated with PFOA, PFOS, PFBS and PFHxA [259][260][261].…”
Section: Animals Experience a Range Of Adverse Effects Usually At Himentioning
confidence: 99%